2009
DOI: 10.12702/1984-7033.v09n01a10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence in Conilon coffee revealed by RAPD markers

Abstract: -This study aimed to evaluate the genetic variability of 49 Coffea canephora clones of the breeding program of the Capixaba Institute of Research, Technical Assistance and Rural Extension (Incaper) based on RAPD markers. Thirty-one primers were used with polymorphism patterns that generated 333 markers, of which 231 (69.4%) were polymorphic. The group of genotypes based on the UPGMA algorithm and Tocher optimization methods detected high divergence in the genotypes. It was found that the component clones of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 9 publications
0
31
1
3
Order By: Relevance
“…RAPD have been used for different number of species, independent of the strategy of reproduction, with success as in Coffea arabica autogamous (Diniz et al 2005); C. canephora allogamous (Ferrão et al 2009), Aspidosperma allogamous (Torezan et al 2005), Zea mays self-fertilized (Souza et al 2008), Catharantus roseus (Shaw et al 2009), Cassava allogamous (Ferreira et al 2008). Chiari et al (2007) highlighted the importance of knowing the genetic variability in the Brachiaria germplasm bank accesses for successful plant breeding plans, planning of divergent crosses and guidance of new collections or germplasm exchange.…”
Section: Ac Ambiel Et Almentioning
confidence: 99%
“…RAPD have been used for different number of species, independent of the strategy of reproduction, with success as in Coffea arabica autogamous (Diniz et al 2005); C. canephora allogamous (Ferrão et al 2009), Aspidosperma allogamous (Torezan et al 2005), Zea mays self-fertilized (Souza et al 2008), Catharantus roseus (Shaw et al 2009), Cassava allogamous (Ferreira et al 2008). Chiari et al (2007) highlighted the importance of knowing the genetic variability in the Brachiaria germplasm bank accesses for successful plant breeding plans, planning of divergent crosses and guidance of new collections or germplasm exchange.…”
Section: Ac Ambiel Et Almentioning
confidence: 99%
“…In these studies a variable number of polymorphic bands was observed, for example, 30 polymorphic bands by Leal et al (2008) and 231 polymorphic bands obtained and evaluated by Ferrão et al (2009). Variation in the number of RAPD markers used in diversity studies is also demonstrated and discussed by Dias et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…The application of RAPD markers is not restricted to the characterization of the genus Passiflora and the use efficiency of this technique in different genetic approaches is demonstrated by recent results in solving problems in different plant species, generating useful information for conservation and genetic improvement of plants (Juchum et al 2007, Leal et al 2008, Ferrão et al 2009). In these studies a variable number of polymorphic bands was observed, for example, 30 polymorphic bands by Leal et al (2008) and 231 polymorphic bands obtained and evaluated by Ferrão et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…A alta diversidade entre plantas de uma mesma lavoura é característica marcante dessa espécie que apresenta alta variabilidade genética natural e polinização cruzada entre gerações (FERRÃO et al, 2009;FONSECA et al, 2006). Essa heterogeneidade, causada pela segregação genética, dificulta os tratos culturais e diminui a produtividade média da lavoura, uma vez que resulta em uma distribuição normal de plantas com maior e menor produtividade de grãos.…”
Section: Introductionunclassified